EVALUASI SISTEM PENGENDALIAN INTERNAL PIUTANG PADA DISTRIBUTOR UNILEVER INDONESIA AREA MANADO - Pondaag, Jones H. Yr; Saerang, David Paul Elia; Affandi, Dhullo (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Good receivable control system will affect the company's success in carrying out the sale on credit policy. Likewise, failure of receivable control an be fatal for the company, for example, many doubtful receivables because weak policies of collection and accounts receivable collection. Purpose which be achieved in this study was to analyze the effectiveness of the internal control system of receivable at Indonesian Distributor of Unilever in Manado Area. The analytical method used is descriptive analysis method, to collect, process, and interpret the data obtained so as to give a true and complete statement describing how internal control of receivable at Indonesian Distributor of Unilever in Manado Area. The results showed that the Internal Control System of Receivable at Indonesian Distributor of Unilever in Manado Area has been going good enough. This distributor has several policies in the provision of receivables. But they do not give any guarantee to customers who want to have credit. And in the provision of distributor accounts to customers based on trust and only based on inputs from the sales. This short coming try anticipated by loyal sales force in collecting accounts receivable to their customers before maturity.